PEMANFAATAN Tyto alba SEBAGAI PENGENDALI HAMA TIKUS DI PERKEBUNAN KELAPA SAWIT DI KABUPATEN KUANTAN SINGINGI - SEPRIDO SEPRIDO; MASHADI MASHADI (Universitas Lancang Kuning, 2019)
Research about the utilization of Tyto alba as rats pest control in oil palm plantations Regency of Kuantan Singingi was done in April-November 2018 in some palm oil plantations in the district of Kuantan Singingi. The methode of this research followto The Barn Owl Protocol, Calculation of the population Tyto alba was directly in area of plantations, counting the number of the prey doing by installation of Camera Trap in artificial enclosure and types of the prey was analysis by skull of the prey in on pellets of Tyto alba. Results of this research show in Kuantan Singingi Regency, The utilization of Tyto alba is still used internally by large private oil palm Plantation, one of Them is PT. Tribakti Sarimas (PT. TBS). On PT. TBS’S oil palm plantations has been using as whole by making a artificial enclosure (Nestbox) 3.000 Unit since 2012 year which spread a cage of for 25 ha on the estate’s core. About 85% of whom had been inhabited by Tyto alba with the evidence she had met the presence of eggs, chicks and eggs have shells.